2020
DOI: 10.2147/prbm.s288562
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Associated with Psychological Distress and Brief Resilient Coping Level During the COVID-19 Pandemic Among Health-Care Professionals in Dessie, Ethiopia</p>

Abstract: Background The outbreak of Coronavirus Disease 2019 (COVID-19) has caused serious threats to people’s health and lives in the world. The health-care professionals are bravely fighting on the front lines of the pandemic everywhere in the world. Our study is the first to study psychological distress and coping status among health-care professionals of Dessie town, Ethiopia during the unbridled time of the COVID-19 outbreak. Methods A cross-sectional internet-based study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…A total of 191 articles were screened for inclusion criteria between the two searches; 32 were selected for this review (Figure 1 ). The studies were conducted from countries worldwide, including China ( n = 11) (Cai et al, 2020 ; Hu et al, 2020 ; Huang et al, 2020 ; Leng et al, 2020 ; Li et al, 2020 ; Liang et al, 2020 ; Lin et al, 2020 ; Liu et al, 2020 ; Lyu et al, 2020 ; Ou et al, 2020 ; Pang et al, 2021 ), Italy ( n = 1) (Catania et al, 2020 ), Iran ( n = 2) (Afshari et al, 2021 ; Meybodi & Mohammadi, 2020 ), France ( n = 1) (Altmayer et al, 2020 ), Japan ( n = 1) (Awano et al, 2020 ), Saudi Arabia ( n = 1) (Balay‐odao et al, 2021 ), the United States, ( n = 3) (Barzilay et al, 2020 ; LoGuidice & Bartos, 2021 ; Resnick, 2020 ), Singapore ( n = 1) (Goh et al, 2020 ), India ( n = 2) (Jose et al, 2020 ; Nathiya et al, 2021 ), Turkey ( n = 3) (Kılınç & Çelik, 2020 ; Yıldırım et al, 2020 ; Yörük & Güler, 2020 ), the Philippines ( n = 1) (Labrague & de los Santos, 2020 ), Canada ( n = 1) (Lapum et al, 2020 ), Spain ( n = 2) (Lorente et al, 2020 ; Luceño‐Moreno et al, 2020 ), the United Kingdom ( n = 1) (Roberts et al, 2021 ) and Ethiopia ( n = 1) (Tsehay et al, 2020 ). A summary of the articles included in this integrative review and their results can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 191 articles were screened for inclusion criteria between the two searches; 32 were selected for this review (Figure 1 ). The studies were conducted from countries worldwide, including China ( n = 11) (Cai et al, 2020 ; Hu et al, 2020 ; Huang et al, 2020 ; Leng et al, 2020 ; Li et al, 2020 ; Liang et al, 2020 ; Lin et al, 2020 ; Liu et al, 2020 ; Lyu et al, 2020 ; Ou et al, 2020 ; Pang et al, 2021 ), Italy ( n = 1) (Catania et al, 2020 ), Iran ( n = 2) (Afshari et al, 2021 ; Meybodi & Mohammadi, 2020 ), France ( n = 1) (Altmayer et al, 2020 ), Japan ( n = 1) (Awano et al, 2020 ), Saudi Arabia ( n = 1) (Balay‐odao et al, 2021 ), the United States, ( n = 3) (Barzilay et al, 2020 ; LoGuidice & Bartos, 2021 ; Resnick, 2020 ), Singapore ( n = 1) (Goh et al, 2020 ), India ( n = 2) (Jose et al, 2020 ; Nathiya et al, 2021 ), Turkey ( n = 3) (Kılınç & Çelik, 2020 ; Yıldırım et al, 2020 ; Yörük & Güler, 2020 ), the Philippines ( n = 1) (Labrague & de los Santos, 2020 ), Canada ( n = 1) (Lapum et al, 2020 ), Spain ( n = 2) (Lorente et al, 2020 ; Luceño‐Moreno et al, 2020 ), the United Kingdom ( n = 1) (Roberts et al, 2021 ) and Ethiopia ( n = 1) (Tsehay et al, 2020 ). A summary of the articles included in this integrative review and their results can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of symptoms of depression was beyond the previous National Health Survey in Ethiopia reported as 22.9% ( Hailemariam et al, 2012 ). Also, it is comparable with the psychological health problems of other frontline fitters, such as healthcare professionals, during the COVID-19 pandemic ( Tsehay et al, 2020 ).…”
Section: Discussionmentioning
confidence: 61%
“…18,23,33,40 Fear of COVID-19 is positively correlated with psychological distress (p=0.638**, p<0.001) as well as insomnia (p=0.444**, p<0.001) which is also observed in similar studies. 18,22,25,29 The Kessler psychological distress scale is positively correlated with ISI (p=0.741%**, p<0.001). Previous study associates distress as a major factor for insomnia leading to burnout among healthcare professionals.…”
Section: Discussionmentioning
confidence: 98%
“…In the study on Ethiopian healthcare professionals, the psychological distress during this pandemic was found out to be 42% and it was 18%, 11%, 13% for the mild, moderate and severe category respectively in the Kessler rating scale. 22 An Egyptian survey of physicians reported 50% of their healthcare workers, predominantly female to be in severe distress during the pandemic while working with a COVID-19 patient. 23 Another study on healthcare workers from Jordan found that 20% of the participants' mainly younger females, dissatisfied with their work had severe distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation